English for Tour Guide in Kotagede: A Needs Analysis of a Situational Language Teaching by Considering their Learning Style - Binawan, Heribertus; Arini, Restu (EDULIA: English Education, Linguistic and Art Journal, 2024)
This research was carried out in Kotagede and the participants in this research were tour guides who worked at the Pendapa Kajengan Kotagede. This study applied the SLT approach or Situational Language Teaching which prioritizes the process of learning a foreign language according to real situations in the field. It applied both quantitative and qualitative to dig out the learning style and the needs for linguistic aspects. The results of this research will give contribution to the best English language teaching method and the most appropriate teaching module. These two things are very important to improve their communication skills with the international tourists. At the end, the increase in English language skills will ultimately affect the quality of their services to the international tourists. Keywords: ESP, Needs Analysis, Tour Guide